PERBANDINGAN PROFITABILITAS PERUSAHAAN SEBELUM DAN SETELAH PENERAPAN UU NO. 40/ 2007 TENTANG KEWAJIBAN PERSEROAN TERBATAS (Studi Empiris pada Perusahaan-Perusahaan yang Bergerak di Bidang Energi dan Sumber Daya Mineral) - Santoso, Yanuar; Rita, Maria Rio (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2012)
Law of the Republic of Indonesia number 40 of 2007 concerning limited liability company requires for every company operate in natural resources to execute corporate social responsibility (CSR). The purpose of CSR is to embrace responsibility for the company’s actions and encourage a positive impact through its activities on the environment, employees, communities, consumers and all other members of the public sphere who may also be considered as stakeholders. Sme previous studies found that CSR could increase financial performanc and gave positive image to communities. This purpose of this study is to test clearly about the difference of firm’s profitability (gross profit margin, operating profit margin, net profit margin, return on assets and return on equity) before and after the requirement of law no. 40/ 2007. The analysis using Wilcoxon signed rank test and using data of financial annual report of firms between 2004 to 2009. Samples consist of mining and mining services companies in Indonesia Stock Market (IDX). The results of this study show that profitabilities of the firms before and after the requirement of law no. 40/ 2007 have no significantly differences. This result probably due to research period is to short, so it can not show significant difference of increase in profit. Keywords: Corporate Social Responsibility, Profitability, Act No. 40/ 2007.